2016
DOI: 10.1063/1.4960298
|View full text |Cite
|
Sign up to set email alerts
|

Dust acoustic double layers in a magnetized dusty self-gravitating plasma with superthermal particles

Abstract: Our prime objective of this paper is to examine the parametric regimes for the existence and polarity of dust acoustic double layers (DADLs) and its solitary structures arising from a magnetized self-gravitating opposite polarity dust-plasma (OPDP) model. The constituents of the OPDP model are two species of positively and negatively charged dust grains, Maxwellian electrons and kappa distributed ions. Contributions of gravitational force only on dust grains are taken into account. For weakly nonlinear analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…These results coincide with those obtained in Refs. [24,30] where α and β have the same effect on the shock wave phase speed, and in the same manner larger β changes the nonlinear term to be negative as is obtained in Fig. 2.…”
Section: Derivation and Solution Of The Kdvb Equationsupporting
confidence: 64%
See 2 more Smart Citations
“…These results coincide with those obtained in Refs. [24,30] where α and β have the same effect on the shock wave phase speed, and in the same manner larger β changes the nonlinear term to be negative as is obtained in Fig. 2.…”
Section: Derivation and Solution Of The Kdvb Equationsupporting
confidence: 64%
“…This Jeans instability was affected by the magnetic field and dust temperature. Later on, Sabetkar and Dorranian [30] found that the increase in the width of the DA double layers resulted due to the considered self-gravitational field enhancement. Sumi et al [32] found also that the amplitude of DA waves was modified by the presence of opposite polarity charged dust and their self-gravitational force.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The works of Mamun and Schlickeiser [40,41] have been further extended to different realistic situations of space and laboratory OPDP systems by a number authors, viz. Sabetkara and Dorranian [42], El-Taibany et al [43], Sumi et al [44], etc. Sabetkara and Dorranian [42] considered the self-gravitating OPDP system containing OPDS, kappa distributed ion species, and Boltzmann electron species to study the DA solitary waves and double layers.…”
Section: Introductionmentioning
confidence: 99%
“…Sabetkara and Dorranian [42], El-Taibany et al [43], Sumi et al [44], etc. Sabetkara and Dorranian [42] considered the self-gravitating OPDP system containing OPDS, kappa distributed ion species, and Boltzmann electron species to study the DA solitary waves and double layers. El-Taibany et al [43] assumed the self-gravitating OPDP system (containing inertial cold OPDS and q-distributed ion as well as electron species) in presence of external magnetic field and polar-ization force acting on OPDS to study the DA periodic and solitary waves.…”
Section: Introductionmentioning
confidence: 99%